MODEL PEMBELAJARAN MATEMATIKA BERBASIS KARAKTER - Mahdiyatus Salami (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2020)
Mathematics can contribute in building logical and critical thinking. As a science that studies abstract objects, it is as if mathematics is a discipline that has little correlation with culture. This raises the assumption that integrating ethnic and cultural content into mathematics is difficult. Though mathematics is a science whose development is also influenced by the socio-cultural context. Therefore, it is possible to teach mathematics by integrating the values of multicultural education. Based on Minister of Education Regulation number 22 of 2006 concerning Standard Content of Mathematics Subjects which contains 5 (five) objectives of mathematics subjects, there are several values of educational character that can be developed through mathematics education in mathematics learning which also includes mathematical characteristics including: discipline, work hard, creative, curious, independent and responsible.